2008
DOI: 10.1158/1535-7163.mct-07-2199
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1 inhibits breast cancer invasion via suppressing the expression of matrix metalloproteinase-9

Abstract: In the present study, we investigated the antitumor effects of the invasiveness and migration of heme oxygenase 1 (HO-1) in human breast carcinoma cells. 12-O-tetradecanoylphorbol-13-acetate (TPA) -induced matrix metalloproteinase-9 (MMP-9) enzyme activity and gene expression at both protein and mRNA levels were examined in human breast carcinoma cells (MCF-7 and MDA-MB-231), and the addition of the MMP-9 inhibitor, SB3CT, significantly suppressed TPA-induced invasion and migration according to the in vitro Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 47 publications
(36 reference statements)
8
77
1
Order By: Relevance
“…PMA has been used as a tumor promoter in chemical-induced carcinogenesis in vitro and in vivo. Previous studies showed that PMA is able to promote tumor migration and invasion by stimulating MMP-2 or MMP-9 expression in glioma, colon, hepatoma, and breast cancer cells [28,29]. However, the mechanism by which PMA induces breast cancer cell invasion has not been known.…”
Section: Discussionmentioning
confidence: 99%
“…PMA has been used as a tumor promoter in chemical-induced carcinogenesis in vitro and in vivo. Previous studies showed that PMA is able to promote tumor migration and invasion by stimulating MMP-2 or MMP-9 expression in glioma, colon, hepatoma, and breast cancer cells [28,29]. However, the mechanism by which PMA induces breast cancer cell invasion has not been known.…”
Section: Discussionmentioning
confidence: 99%
“…However, HMOX-1 can induce cancer cell apoptosis and inhibit tumor cell motility. 30,31 Recently, HMOX-1 expression was shown to be elevated by PL in breast cancer cells and a determining factor in the differential response of normal breast cells to PL. 32 Interestingly, PL silenced ATP-binding cassette subfamily B, member 10 (ABCB10) expression.…”
Section: Discussionmentioning
confidence: 99%
“…Given that HO-1 represses MMP-9 activation during the inhibition of breast cancer progression (Lin et al 2008), it is opening the possibility that BMP-6 induction is, at least partially, responsible for the down-regulation of MMP-9 expression. Therefore, we detected BMP-6-regulated expression of MMP-9 in MCF-7 cells.…”
Section: Bmp-6 Activates Ho-1 Transcription In a Smad-dependent Mannermentioning
confidence: 99%